Fenia Meroh: Jaringan Pengetahuan Perempuan dalam Pendidikan Adat Orang Tambrauw - Yuliana Arsyad; bustamin wahid; hartinah idrus (Universitas Muhammadiyah Sorong, 2021)
The purpose of this research was to find out the meaning of women's knowledge in the indigenous education of Fenia Meroh, Tambrauw people. This research used descriptive qualitative method, with a specific case study approach that examines a case study in community life. As for the data collection technique by using Non-participatory observation Non-participation observation, interview and documentation. Data Analysis Techniques Furthermore, from the types of research above, the researcher used an interactive model from Miles and Huberman, (2014: 14) to analyze the research data. The results of this study showed that the Fenia Meroh indigenous education encourages humans to understand eating about civilized and perfect humans. With the rules and ideals, humans do not harm fellow humans and the universe as the source of life. Not to mention the natural contemplation process carried out by the people in Tambrauw, they are familiar with initiation education, that container then divides into two fenia meroh education (women's learning) and mber ion education (men's learning). Sacred rituals and processions to become superior and intelligent human beings without the legitimacy of the State are an end in a path of silence.